`f(x)=1/(2+x)^3` Use the binomial series to find the Maclaurin series for the function.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Recall a binomial series  follows: 

`(1+x)^k=sum_(n=0)^oo _(k(k-1)(k-2)...(k-n+1))/(n!)x^n`

or

`(1+x)^k = 1 + kx + (k(k-1))/(2!) x^2 + (k(k-1)(k-2))/(3!)x^3 +(k(k-1)(k-2)(k-3))/(4!)x^4+` ...

To evaluate given function `f(x) =1/(2+x)^3` , we may apply  `2+x = 2(1+x/2)` .

The function becomes:

`f(x) =1/(2(1+x/2))^3`

Apply Law of Exponents: `(x*y)^n = x^n*y^n` at the denominator side.

`1/(2(1+x/2))^3=1/(2^3(1+x/2)^3)`

                `= 1/(8(1+x/2)^3)`

Apply Law of Exponents: `1/x^n = x^(-n)` .

`f(x) = 1/8(1+x/2)^(-3)`

Apply the binomial series on `(1+x/2)^(-3)` . By comparing "`(1+x)^k` " with "`(1+x/2)^(-3)` " the corresponding values are:

`x=x/2 ` and` k =-3`

Then,

`(1+x/2)^(-3) =sum_(n=0)^oo _((-3)(-3-1)(-3-2)...(-3-n+1))/(n!)(x/2)^n`

` =1 + (-3)x/2 + ((-3)(-3-1))/(2!) (x/2)^2 + ((-3)(-3-1)(-3-2))/(3!)(x/2)^3 +((-3)(-3-1)(-3-2)(-3-3))/(4!)(x/2)^4+...`

` =1 -(3x)/2 + ((-3)(-4))/(2!) (x^2/4) + ((-3)(-4)(-5))/(3!)(x^3/8) +((-3)(-4)(-5)(-6))/(4!)(x^4/16)-` ...

` =1 -(3x)/2 +12/(2!) (x^2/4) -60/(3!)(x^3/8) +360/(4!)(x^4/16)-` ...

`=1 -(3x)/2 +(3x^2)/2 -(5x^3)/4 +(15x^4)/16-` ...

Applying `(1+x/2)^(-3) =1 -(3x)/2 +(3x^2)/2 -(5x^3)/4 +(15x^4)/16-` ..., we get:

`1/8(1+x/2)^(-3)=1/8*[1 -(3x)/2 +(3x^2)/2 -(5x^3)/4 +(15x^4)/16-...]`

                    `=1/8-(3x)/16 +(3x^2)/16 -(5x^3)/32 +(15x^4)/128-` ...

Therefore, the Maclaurin series  for  the function `f(x) =1/(2+x)^3` can be expressed as:

`1/(2+x)^3=1/8-(3x)/16 +(3x^2)/16 -(5x^3)/32 +(15x^4)/128-` ...

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial